Pesantren Sebagai Penangkal Radikalisme dan Terorisme - Ari Prayoga; Mohammad Sulhan (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
Today the discussion of radicalism is often associated with Muslims. The pesantren as an Islamic educational institution is the foundation of the ummah to spread peace and introduce to Islamic brothers and sisters among the pesantren. This paper intends to offer ideas on efforts to increase the role of pesantren as a stronghold to counter the development of radical understanding and action in their environment. This idea was formulated based on three things: first, the philosophy and tradition of pesantren; second, facts found about the understanding that developed in pesantren and third, the analysis of the stages and factors that can make someone who has a radical understanding can be dragged into radical actions.